Au/TiO2 2D‐Photonic Crystals as UV–Visible Photocatalysts for H2 Production. Issue 6 (29th December 2021) - Torras, Miquel; Molet, Pau; Soler, Lluís; Llorca, Jordi; Roig, Anna; Mihi, Agustín
Abstract: Noble metal decoration of wideband gap semiconductors enables the excitation of surface plasmons in the visible range that upon relaxation generate hot carriers used for catalysis. However, this strategy leads to photocatalytic conversion efficiencies that are still low. Here, a light‐trapping scheme is used to amplify the light‐harvesting efficiency of the TiO2 semiconductor beyond the UV region by coupling a 2D‐photonic crystal to Au decorated titania. This approach is easily scalable using soft nanoimprinting lithography to prepare Au/TiO2 2D‐photonic photocatalysts. In a first process, gold nanoparticles (Au NPs) are in situ infiltrated in the superficial 50 nm of a mesoporous titania (mTiO2 ) scaffold patterned with the photonic structure, while in a second one 2D‐photonic crystals with a homogeneous volume distribution of the Au colloids are achieved. The dependence of the optical properties of the photonic crystals on the lattice parameter, geometry, and metal loading is presented through extinction measurements and analyzed through simulations. The improved photocatalytic performance of the substrates is tested for hydrogen production where a maximum of 8.5 mmol gcat −1 h −1 of H2 is recorded and attributed to photonic–plasmonic effects. These results may open new avenues in solar harvesting for hydrogen production using photonic crystals as photocatalysts. Abstract : The photocatalytic efficiency of titanium dioxide is extended into the visible region by combining the light‐trapping properties of a 2D‐photonic crystal and the plasmonic resonances of gold colloids. The scalable Au/TiO2 2D‐photonic photocatalysts show a maximum hydrogen production of 8.5 mmol gcat −1 h −1 attributed to photonic–plasmonic effects.